INOVASI PEMBELAJARAN ABAD 21 DENGAN PENDEKATAN SAINTIFIK DAN MODEL KOOPERARIF TIPE STAD - Nadya Amalia Juana; Jailani Jailani; Junet Kaswoto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Learning to know, learning to do, learning to be, and learning to live together are all connected to the four pillars of education. In order to achieve the pillars of education, it is necessary to adapt to the current learning trend of cooperative learning and innovate learning. Using a scientific method and a cooperative learning model similar to STAD, the goal of this study is to make it more likely that students will be able to develop skills relevant to the modern world. With a total sample of 25 students, a quasi-experimental design was used for the research. Tests, questionnaires, observation sheets, and other methods of data collection are utilized. This study's findings demonstrate how STAD-style cooperative learning and a scientific approach support 21st-century students' skills and influence learning achievement. so that students' problem-solving, critical thinking, mathematical communication, and collaboration abilities will all benefit from the STAD learning model's implementation.